Test on Mineral Processing Technology for the Copper-iron Ore - Linzhu REN; Lipeng WANG; Baoshan LIU (Kuangchan zonghe liyong)
Aiming at the characteristics of a copper-iron ore, we adopt the process of first flotation and then magnetic process, together with the use of ester-112, which is a good selective collector, to realize the comprehensive recovery of the ore. Using the “first flotation - then magnetic” process, the original ore is ground to -74 μm 70%, copper circuit using one roughing, three cleaning for the output of copper concentrate.copper sweeping tailings after a magnetic separation output of iron ore concentrate. Closed-circuit tests obtained copper grade of 20.72% and recovery rate of 80.76% in the copper concentrate, gold grade of 43.91 g/t and recovery rate of 86.29% in the copper concentrate, iron grade of 66.38% recovery rate of 94.20% in the iron concentrate, among which the content of the harmful elements of the sulfur is only 0.16%.